Improved SOR signal detection algorithm in massive MIMO-TRDMA systems - Mingyue WANG; Fangwei LI; Xiaorong JING; Haibo ZHANG; Junzhou XIONG (Tongxin xuebao)
In the massive multi-input multi-output time-reversal division multiple access (MIMO-TRDMA) systems, the traditional linear minimum mean square error (MMSE) algorithm achieved approximately the best performance.However, the matrix inversion of the MMSE algorithm was too complicated to ensure real-time processing of signal detection.To solve this problem, an improved successive over-relaxation (SOR) signal detection optimization algorithm was proposed.The proposed algorithm reasonably upgraded the solution of linear equations to prevent the complicated calculation of matrix inversion.Meanwhile, the steepest descent idea was used to provide an effective search direction for the SOR signal detection algorithm, achieving a rapid convergence rate and stronger inspection performance.The simulation results show that the proposed algorithm has the similar best performance with fewer update times compared with the traditional MMSE algorithm, and the calculation complexity is reduced from O(M3)to O(2).